PERANAN ADVOKAT DALAM PROSES DIVERSI ANAK YANG BERKONPLIK DENGAN HUKUM PADA TINGKAT PEMERIKSAAN DI KEPOLISIAN - Latief Hasjim (Justici, 2021)
This writing mainly aims to provide information, especially regarding the rights of children as perpetrators of criminal acts, during the investigation process at the police level. The problems that the writer raises in this thesis are related to diversion arrangements and implementation constraints. To find answers to problems, approach Law no. 8 of 1981 concerning the Criminal Procedure Code and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which specifically regulates diversion, objectives and procedures for implementing diversion. Even though diversion has a good purpose, in its implementation there are still obstacles, such as unprofessional investigators, incomplete facilities, very weak public knowledge and awareness, so to guarantee that diversion can be implemented there needs to be provisions regulating criminal sanctions against investigators which does not implement diversion.